Challenging the great equalizer a study on the impact of natural disasters on income inequality across the regions in the Philippines - Ceniza, Samantha Yzavelle H. (School of Economics, University of the Philippines Diliman, 2018)
The Philippines is often at high risk from natural disasters. Indeed, the data show that there is an increasing trend in the number and magnitude of disasters in the country in the last century. While, it is often argued that natural disasters are the _great equalizers_ of mankind as they affect everyone equally, there is evidence that disasters may disproportionately adversely affect the poor, and may even result in a worsening of income inequality. As such, this paper focuses on investigating the relationship between natural disasters and income inequality in the Philippines. Using panel data analyses on a dataset of 17 regions spanning ten three-year intervals from 1985 to 2015, our results show that the presence of a natural disaster is positively associated with income inequality, measured by the gini coefficient. However, when we decompose by type, we find evidence that Geophysical, Meteorological, and Hydrological disasters increase income inequality but Climatological disasters tend to reduce income inequality. There is also evidence that disasters have short_term (3 years) and long_term (6 years) effects on income inequality. Furthermore, we decompose the gini coefficient of the mean per capita income by income source to verify how inequality by specific income source associates with natural disasters and estimation results reveal that disasters decrease Remittance inequality _ providing additional evidence for the _buffering effect_ of remittances _ but increase other income sources inequality (i.e. Agricultural, Non-Agricultural, Entrepreneurial, Other Income).